Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1074/jbc.m802323200
|View full text |Cite
|
Sign up to set email alerts
|

Role of N-Acetylglucosaminidase and N-Acetylmuramidase Activities in Enterococcus faecalis Peptidoglycan Metabolism

Abstract: Identification of the full complement of peptidoglycan hydrolases detected by zymogram in Enterococcus faecalis extracts led to the characterization of two novel hydrolases that we named AtlB and AtlC. Both enzymes have a similar modular organization comprising a central catalytic domain fused to two LysM peptidoglycan-binding modules. AtlB and AtlC displayed N-acetylmuramidase activity, as demonstrated by tandem mass spectrometry analyses of peptidoglycan fragments generated by the purified enzymes. The genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
99
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(101 citation statements)
references
References 30 publications
2
99
0
Order By: Relevance
“…Similar long-pulse-chase experiments have revealed that other ovococcus-shaped bacteria, such as Enterococcus faecalis and Streptococcus mutans, exhibit low rates of PG fragment release from sacculi (56,57). One interpretation of these combined results is that there is minimal PG turnover and PG fragment release in exponentially growing S. pneumoniae and, likely, in other Gram-positive ovococcus species compared to the PG turnover and fragment release in B. subtilis.…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…Similar long-pulse-chase experiments have revealed that other ovococcus-shaped bacteria, such as Enterococcus faecalis and Streptococcus mutans, exhibit low rates of PG fragment release from sacculi (56,57). One interpretation of these combined results is that there is minimal PG turnover and PG fragment release in exponentially growing S. pneumoniae and, likely, in other Gram-positive ovococcus species compared to the PG turnover and fragment release in B. subtilis.…”
Section: Resultsmentioning
confidence: 71%
“…Thus, minimal turnover is a general property of the PG of growing S. pneumoniae cells. There may also be minimal PG turnover in other ovococcus species, based on an apparent absence of recycling enzymes and results from previous radiolabeling experiments showing low rates of PG fragment release from sacculi (13,56,57).…”
Section: Figmentioning
confidence: 99%
“…Binding to three sites was not associated with changes in the expression of proximal genes, as determined by comparing the transcript levels of the wild-type strain to those of the rgg mutant strain (Table 3); however, binding to the other three sites was associated with changes in the expression of the downstream ORFs (19). These binding sites were upstream of spd-3, which is carried by prophage NZ131.3; a gene encoding an integrase/excisionase (Spy49_0746) carried by prophage NZ131.2; and a gene encoding a surface antigen (Spy49_0396), which has a motif present in lysins (Table 3) (5,6,24,38) and is carried by prophage NZ131.3. Differences in the expression of the prophage integrase between the rgg mutant and the wild-type strain were previously associated with changes in the frequency of prophage excision from the genome (19).…”
Section: Identification Of Rgg Binding Sites In Vivomentioning
confidence: 99%
“…Two autolysins of Staphylococcus epidermidis, AtlE and Aae, are adhesins that contribute to bacterial attachment to polymeric surfaces and biofilm formation via release of eDNA (20,21,58). E. faecalis produces several autolysins, which were recently identified and characterized (12,24,35). The major E. faecalis autolysin, Atn (also known as AtlA), is an N-acetylglucosaminidase important for daughter cell separation during cellular division (12).…”
mentioning
confidence: 99%